IMPLEMENTASI MANAJEMEN BANDWITH DENGAN METODE SIMPLE QUEUE MENGGUNAKAN MIKROTIK PADA PT. ANUGERAH JAYA REALTY: IMPLEMENTATION OF BANDWITH MANAGEMENT WITH SIMPLE QUEUE METHOD USING MICROTIK AT PT. ANUGERAH JAYA REALTY - SETYANTO, WICAKSONO; Nainggolan, Esron Rikardo (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
Computer networks and the internet are becoming necessities for offices in the modern era. Similar to this, PT. Anugerah Jaya Realty already has a computer network and access to the internet. However, these systems have not performed to their full potential because bandwidth management using a Mikrotik router, which aims to help overcome the density of traffic and the competition for bandwidth between one client computer and other clients who can interfere with existing computer network connections, has not been done. It is required to alter bandwidth management in order to obtain the proper bandwidth capacity information for each client when the network is down or the computer network is experiencing issues since there is not a consistent bandwidth allocation for each user. The available bandwidth will then be distributed equally across all currently active clients in order to maximize it. There are various stages to the installation of bandwidth management, including computer network design, testing, implementation, and testing, The results obtained after the implementation and testing are completed is that now the computer network connected to the internet has bandwidth stability.